2021
DOI: 10.1515/nanoph-2021-0114
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional planar topological laser

Abstract: Topological interface states are formed when two photonic crystals with overlapping band gaps are brought into contact. In this work, we show a planar binary structure with such an interface state in the visible spectral region. Furthermore, we incorporate a thin layer of an active organic material into the structure, providing gain under optical excitation. We observe a transition from fluorescence to lasing under sufficiently strong pump energy density. These results are the first realization of a planar top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Moreover, it has been theoretically suggested that the cavity modes of VCSELs 18,19,27 are mathematically equivalent to topological surface or edge states 28 . The thickness of the gain medium (including a spacer layer 29 ) in such a Fabry-Pérot cavity laser is bound to be an integer multiple N of half the emission wavelength (d = λ g 2 N, N = 1,2,3…) to fulfill the condition of constructive interference of the resonance in the cavity.…”
Section: Tunable Topological Interface-state Cavity Lasersmentioning
confidence: 99%
“…Moreover, it has been theoretically suggested that the cavity modes of VCSELs 18,19,27 are mathematically equivalent to topological surface or edge states 28 . The thickness of the gain medium (including a spacer layer 29 ) in such a Fabry-Pérot cavity laser is bound to be an integer multiple N of half the emission wavelength (d = λ g 2 N, N = 1,2,3…) to fulfill the condition of constructive interference of the resonance in the cavity.…”
Section: Tunable Topological Interface-state Cavity Lasersmentioning
confidence: 99%
“…proposed a scheme to predict the OTS by exploiting the connection between the optical Tamm states and photonic bulk band topology. [ 8 ] A broad variety of applications is possible with topological OTS in areas such as lasing, [ 9 ] sensing, [ 10 ] communication, photodetection, [ 11 ] and so on. Tamm plasmon‐based absorber has been extensively studied in these fields.…”
Section: Introductionmentioning
confidence: 99%
“…topology. [8] A broad variety of applications is possible with topological OTS in areas such as lasing, [9] sensing, [10] communication, photodetection, [11] and so on. Tamm plasmon-based absorber has been extensively studied in these fields.…”
mentioning
confidence: 99%
“…[10][11][12] Topologically engineered photonic crystal structures are efficient platforms for lasing action, wherein emission is achieved at a relatively low pump threshold. 13,14 Photonic band gap (PBG) structures are the right candidate to fabricate devices ranging from microwaves to the visible range of the electromagnetic spectrum. A one-dimensional photonic crystal (1D PC) is a heterogenous multilayer structure periodic in one direction controlling propagating light.…”
Section: Introductionmentioning
confidence: 99%